Laparoscopic diverting loop ileostomy for spontaneous colon perforation in advanced ovarian cancer - John O. Schorge (Elsevier, 2019)
Objective: Neoadjuvant chemotherapy for advanced ovarian cancer is associated with reduced morbidity in the elderly (Meyer et al., 2018). Spontaneous colonic perforation often leads to multisystem organ failure and death (Carter and Durfee, 2007; Rose and Piver, 1995). Methods: A 76-year old woman with stage IIIC disease initiated carboplatin AUC 5 and paclitaxel 175 mg/m2 with unanticipated development of profound neutropenia. She clinically deteriorated by day nine and CT scan revealed a large volume of free air. Emergent surgery was performed. Results: Diagnostic laparoscopy confirmed the presence of intra-abdominal stool and extensive inflammatory exudate (Video). The likelihood of identifying the site of perforation appeared remote, but pelvic tumor encasement was highly suggestive of a sigmoid origin. The stool was evacuated, the exudate gently debrided and the terminal ileum partially mobilized. Copious irrigation was performed with drain placement and the pneumoperitoneum was decompressed. The right lower abdominal wall trocar incision was extended so that the ileal segment could be brought out and matured. She was discharged to rehab on postoperative day 2 to continue a two week course of broad spectrum antibiotics. Single-agent carboplatin was resumed within a month. Uncomplicated ileostomy takedown with parastomal hernia repair was performed between cycles five and six. The patient is currently in remission. Conclusion: Bowel perforation in the elderly, presenting with cachexia and treatment-induced pancytopenia for advanced ovarian cancer, is often a harbinger of early death. Selected patients may benefit from a minimally invasive approach by an experienced gynecologic oncologist instead of vertical laparotomy, abdominal washout, diversion and the potential sequelae of an open abdomen. Keywords: Advanced ovarian cancer, Paclitaxel-induced colon perforation, Minimally invasive surgery, Diverting loop ileostomy